The Structural Thermal Stability of the Fe80Si7 B13 Alloys Under the Irradiation of High-Intensity Pulsed Ion Beam; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Xiaonan Zhang; Tong Guan; Xianxiu Mei; Younian Wang; Remnev G. E. Gennady Efimovich; Pavlov S. K. Sergey Konstantinovich (2019, 2019)
Заглавие с экрана